2008
DOI: 10.1002/ppul.20885
|View full text |Cite
|
Sign up to set email alerts
|

Safety of bronchoalveolar lavage in young children with cystic fibrosis

Abstract: Adverse events are common with BAL in young CF children, but are usually transient and well tolerated. Parents should be counseled that signs of a pre-existing lower respiratory infection are associated with increased risk of post-BAL fever.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 28 publications
(51 reference statements)
3
17
0
1
Order By: Relevance
“…(64) Bronchoscopic evaluation has shown heterogeneity of distal airway drug deposition among children of different ages. Although generally safe, (65) flexible bronchoscopy does require anesthesia in young children and, thus, results in healthy controls may be unobtainable due to restrictions from institutional review boards. Notable limitations of using bronchoscopy to study aerosol deposition include the fact that BAL fluid samples are typically obtained from one or two lobes and, thus, present with an inherent sampling error.…”
Section: Flexible Bronchoscopymentioning
confidence: 98%
“…(64) Bronchoscopic evaluation has shown heterogeneity of distal airway drug deposition among children of different ages. Although generally safe, (65) flexible bronchoscopy does require anesthesia in young children and, thus, results in healthy controls may be unobtainable due to restrictions from institutional review boards. Notable limitations of using bronchoscopy to study aerosol deposition include the fact that BAL fluid samples are typically obtained from one or two lobes and, thus, present with an inherent sampling error.…”
Section: Flexible Bronchoscopymentioning
confidence: 98%
“…Patients are reviewed every 2 to 3 months with sputum or cough swab specimens each visit. Patients under 6 years were enrolled in a randomised controlled trial of broncho-alveolar lavage (BAL) guided therapy (1999)(2000)(2001)(2002)(2003)(2004)(2005) [12,13] or the AREST CF programme (www.ARESTCF. com.au) which included broncho-alveolar lavage (BAL) soon after diagnosis and annually.…”
Section: Settingmentioning
confidence: 99%
“…Eight studies out of those included in this review were found to describe short-term (hours or days) adverse events related to BAL procedures [6,8,22,50,52,54,64,65] (table E6). Reported adverse events were mainly mild, for example mild fever, worsening of cough, mild respiratory distress or stridor.…”
Section: Feasibility and Safetymentioning
confidence: 99%
“…Of note, BAL has been extensively studied in children (.333 procedures in 107 infants in one study [65]), but not adults, in particular in the presence of very altered lung function (FEV1 ,40%) [13,22,26,52,65]. In this latter subgroup of patients, the volume recovered may be decreased and the risk of the procedure increased.…”
Section: Group Consensus On Feasibilitymentioning
confidence: 99%